Krüppel-Like Factor 10 participates in cervical cancer immunoediting through transcriptional regulation of Pregnancy-Specifc Beta-1 Glycoproteins - Marrero-Rodríguez, Daniel (2018)
Cervical cancer (CC) is currently the second most common cancer among the female population1 . As is the case with many other cancer types, host immune system evasion, involving the failure of the immune system to resist or eradicate formation and progression of incipient neoplastic cells, late-stage tumors and micro-metastasis is problematic in CC2 . Te host immune response evasion by Human Papilloma Virus (HPV) associated CC has been reviewed elsewhere3 . Cytokines such as Interleukin (IL) 10, IL13 and transforming growth factor β (TGFβ) are known to be involved in evasion of CC from the immune system response3,4 . Tumor-associated infammation and the infammatory components present in the tumor microenvironment are also recognized as having a role in tumor development5 . Tis is mediated in part through the supply of bioactive molecules to the tumor microenvironment. Tese include growth factors, survival factors, pro-angiogenic factors, extracellular matrix-modifying enzymes, as well as the inductive signals that lead to activation of epithelial-mesenchymal transition (EMT)2 . Tis phenomenon is orchestrated by a plethora of cytokines and chemokines. In CC, cytokines such as IL6, −86 and Cervical cancer (CC) is currently the second most common cancer among the female population1 . As is the case with many other cancer types, host immune system evasion, involving the failure of the immune system to resist or eradicate formation and progression of incipient neoplastic cells, late-stage tumors and micro-metastasis is problematic in CC2 . Te host immune response evasion by Human Papilloma Virus (HPV) associated CC has been reviewed elsewhere3 . Cytokines such as Interleukin (IL) 10, IL13 and transforming growth factor β (TGFβ) are known to be involved in evasion of CC from the immune system response3,4 . Tumor-associated infammation and the infammatory components present in the tumor microenvironment are also recognized as having a role in tumor development5 . Tis is mediated in part through the supply of bioactive molecules to the tumor microenvironment. Tese include growth factors, survival factors, pro-angiogenic factors, extracellular matrix-modifying enzymes, as well as the inductive signals that lead to activation of epithelial-mesenchymal transition (EMT)2 . Tis phenomenon is orchestrated by a plethora of cytokines and chemokines. In CC, cytokines such as IL6, −86 and Cervical cancer (CC) is currently the second most common cancer among the female population1 . As is the case with many other cancer types, host immune system evasion, involving the failure of the immune system to resist or eradicate formation and progression of incipient neoplastic cells, late-stage tumors and micro-metastasis is problematic in CC2 . Te host immune response evasion by Human Papilloma Virus (HPV) associated CC has been reviewed elsewhere3 . Cytokines such as Interleukin (IL) 10, IL13 and transforming growth factor β (TGFβ) are known to be involved in evasion of CC from the immune system response3,4 . Tumor-associated infammation and the infammatory components present in the tumor microenvironment are also recognized as having a role in tumor development5 . Tis is mediated in part through the supply of bioactive molecules to the tumor microenvironment. Tese include growth factors, survival factors, pro-angiogenic factors, extracellular matrix-modifying enzymes, as well as the inductive signals that lead to activation of epithelial-mesenchymal transition (EMT)2 . Tis phenomenon is orchestrated by a plethora of cytokines and chemokines. In CC, cytokines such as IL6, −86 and as well as chemokines such as CCL28 are known to exert these pro-infammatory efects. Expression of these molecules in the tumor microenvironment is tightly regulated by transcription factors. Krüppel like factors (KLF’s) are a family of transcription factors that participate in various aspects of cellular growth, proliferation and diferentiation9 . Tis family is characterized by three C2H2-type zinc fnger domains that bind to either CACCC elements or GC boxes in the promoter of target genes to regulate transcriptional activity and gene expression9 . Recently, we have reported the expression of several members of the KLF family in CC including KLF1010. KLF10 can function as a trans-activator or –repressor11. It has been previously reported that KLF10 is expressed in several tissues and various cell types that include smooth muscle, heart, glial cells, fbroblasts, myeloid cells12, and lymphoid cells11. Gene-targeting studies have implicated important roles for KLFs in immune and hematopoietic cell biology. For example, in CD4+CD25− cells, KLF10 is known to play an important role in T-cell activation and diferentiation as well as Treg suppressor functions through regulation of TGFβ11. It has been reported that KLF10 can also directly regulate the pro-infammatory cytokine IL12p4013. In addition to the above-mentioned functions of KLF10 in multiple cell and tissue types, no one has implicated a role for KLF10 in CC. In this report we have analyzed the molecular alterations of KLF10 in CC and have identifed potential KLF10 target genes by means of DNA copy number variation (CNV) and mRNA transcription using microarrays, in silico analyses and putative transcriptional regulatory networks using gene knock-down approaches in vitro and in vivo.